Hernia Traumatik Dinding Abdomen Pada Kucing Ras Mix - Apritya, Desty; Rahman, Mohammad Noor; Latif, Annisa Catria; Yuyun, Maria Ernestina; Nahak, Ivonia Maya Paula; Mahpuz, Fajar Aulia; Hanapi, Muhammad Iqbal; Murtado, Murtado (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
Abdominal wall hernia is a protrusion of the abdominal contents through an abnormal ring or hole in the abdominal cavity of the body. A mixed breed female cat, 3 years old, weighing 2.5 kg, complaining of a lump in the left lateral abdominal area accompanied by a ring with a mass that can be pushed in. Based on the history, the protrusion is approximately 3 weeks and is thought to be caused by trauma. The results of a complete blood count showed normal results. Accompanied by the results of the x-ray examination, the patient was diagnosed with a traumatic hernia of the abdominal wall with a faustal prognosis. Case management involves repositioning the content into the abdominal cavity and suturing the hernia ring. Postoperative therapy was given injection cefotaxime antibiotics followed by amoxicilline (20 mg / kg BW; q 12h; for 5 days), anti-pain mefenamic acid (for 5 days), and Vitamin B, C (until patient healed).